A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 XIII KOTO KAMPAR IN COMPREHENDING NARRATIVE TEXTS - Irna Yanti; Fadly Azhar; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed at finding out how the ability of the second year students of SMAN 1 XIII Koto Kampar in comprehending narrative texts.The design of the research was one class for try out test and one class for real test. The population was the second year students at second semester of academic year 2016/2017. The sample was 29 students of class XI IPS 1 which were chosen by usinglotre. The data were collected by giving 8 narrative texts in form 40 multiple choices. The results of the data analysis showed that the mean score of the students’ ability in compreheneding narrative texts is 64,48. It means that the ability of the second year students of SMAN 1 XIII Koto Kampar in comprehending narrative texts categorized into good level.Keywords: Ability, Reading Comprehension, Narrative Text.